Special Issue – Signalling. Introduction – Ca2+ signalling and transport in health and disease. (23rd September 2013) - Tidow, Henning; Nissen, Poul
<x xml:space="preserve">Abstract</x> This series of articles in the FEBSJournal Special Issue on Signalling is based on the international symposium 'Ca2+ Signalling and Transport in Health and Disease', Aarhus, 2012. A mixture of research articles and reviews cover a broad range of calcium signalling and transport‐related topics. An accompanying series entitled Frontiers in Cell Signalling is based on the 6th Garvan Signalling Symposium, Sydney, 2012. <boxed-text content-type="graphic" id="febs12507-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>